Partial Characterization of Salmonella gallinarum Clinical Isolate and Expression of Its Antigenic Outer Membrane Protein C (ompC) Gene in planta - Pang, Ee Leen; Loh, Hwei-San (Journal of Tropical Life Science, 2015)
Instigating approximately 100% of mortality and morbidity rates, fowl typhoids epidemiology and disease intervention have been extensively studied since 1950s. Even up-to-date, outbreaks are incessantly haunting poultry industries of major continents. Salmonella gallinarum, the etiologic agent of fowl typhoid, was used to develop a series of vaccination regime. However, treatments are gradually losing effectiveness due to residual virulence from mutated strains and rapid evolution of multi-drug resistance isolates. Hence, in planta subunit vaccine production is proposed to surpass current limitations. The homotrimeric osmoporin (Outer Membrane Protein C) is a potent candidate antigen that confers momentous stimulation of humoral and cell-mediated immune responses in broilers. This research signified the potential development of plant-expressed ompC immunogen, with the scope embarked on identification of S. gallinarum clinical isolate; construction of expression cassette; generation of recombinant vector and delivery of constructs into Nicotiana benthamiana for transient expression via agroinfiltration. The ompC transcripts and proteins were detected successfully at the molecular weights of 1.002 kbp and 35 kDa, respectively. These preliminary findings pave the feasibility of biomanufacturing a safe and cost-effective fowl typhoid vaccine that would confer multi-protection against other significant Salmonella infections attributed to high sequence homology of ompC gene. Speed improvement is demonstrated and transient expression appears to outperform conventional platforms in expediting vaccine production for an emerging pandemic strain.